Turkish Dialect Implementation of the Stroop Task - Uzun, Cemile; Eraydin, Yelda Yesildal (My University, 2025)
This study investigates the effect of language on cognitive control and attention processes in speakers of different Turkish dialects using the Stroop task. It differs from other studies investigating the Stroop task in the language domain in that it investigates the Stroop task across Turkish dialects. Specifically, the study aims to show how the Stroop effect works in different dialects of Turkish. For this purpose, Kazakh and Turkmen participants learning Turkish were administered the Stroop task. The choice of Kazakh and Turkmen dialects of Turkish was based on their close linguistic relationship to Turkish and the linguistic background of the participants. In the Stroop task, participants were presented with coloured words printed in either congruent or incongruent colours. The results showed that Turkmen and Kazakh participants responded slower in the incongruent condition, but had faster response times in the congruent condition. Furthermore, accuracy rates differed between the two groups, with Turkmen participants generally achieving higher correct response rates. These findings suggest that the strategies of reducing cognitive load and adding control cues are differentially effective across dialect groups.
Keywords: Kazakh; Turkmen; dialects; stroop task